In silico study of Bacillus spB201 amylase through protein sequence inspection - Sameh Ben Mabrouk; Bouthaina Ben Hadj Hmida; Ikram Boukthir; Slim Cherif (Journal of the Arab Society for Medical Research)
Background/aim Bioinformatics is the automatic processing of biological information, and it is a helpful tool to study the structure-function relationship of various proteins. Here, it was used in the in silico study of an AmyB201 from Bacillus strain, named AmyB201 to describe its origin and properties, which could help us to improve the performance of this enzyme through mutagenesis. Materials and methods The protein sequence of AmyB201 was purchased from NCBI data Base. The Signal P and the Protparam were used to determine the properties of AmyB201. In addition, programs like Swiss-model, Phyre2 and PyMOL were used to generate and manipulate the AmyB201 models. Results Comparaison study of Amy B201using Blast program showed an identity of 94% and 91% with amylases from Bacillus spUS586 and Bacillus spUS572, respectively. Subsequently, the analysis of the sequence by the Signal P. program revealed the presence of a signal peptide, which confirms the extracellular nature of the enzyme. Furthermore, the examination of the AmyB201 sequence by Espript showed that it has the same secondary structure with amylases from Bacillus spUS586 and Bacillus spUS572, with the exception of a few differences that could explain the specificity of each enzyme. In addition, the inspection of the 3D models showed the presence of three typical domains of amylases, namely the domains: A, B, C. Using these structures, we have been able to explain some properties of AmyB201. Conclusion This study was able to describe the origin of some properties of AmyB201, and could help us to improve the performance of this enzyme through mutagenesis.